Kontaminasi Escherichia coli pada Makanan Jajanan di Kantin Universitas Muhammadiyah Sidoarjo: Contamination of Escherichia coli in Snacks at the Canteen of Muhammadiyah University of Sidoarjo - Rohmah, Jamilatur; Rini, Chylen Setiyo; Cholifah, Siti (Medicra (Journal of Medical Laboratory Science/Technology), 2018)
One of the places to get food is in the cafeteria. Food made in the canteen can be a cause of foodborne desesase and food poisoning if not properly disposed. The objective was to analyse the quality of food microbiology on canteen food in campus 1, 2, and 4 University Muhammadiyah of Sidoarjo. This study applied the descriptive observational which cross sectional design in canteen food stalls and sampling technique which is total sampling. Tests of canteen food samples were performed using Total Plate Count (TPC). A total of 35 samples of canteen foods from the campus canteen. The results show that positive E.coli contamination on canteen food (canteen campus 1, 2, and 4) was 25 (71.43%). There is a significant difference from the burden of microbial samples of canteen food. This research was conducted to find out personal hygiene and environment, and the cleanliness of the campus should be improved and maintained.